PENGARUH PENERAPAN PROGRAM ADAPTASI CHSE (CLEANLINESS, HEALTH, SAFETY, ENVIRONMENT) TERHADAP KEPUASAN PENGUNJUNG DESTINASI WISATA KABUPATEN KEDIRI DI ERA NEW NORMAL SERTA DAMPAKNYA PADA PENGEMBANGAN EKONOMI PARIWISATA & INDUSTRI KREATIF - Fitri Arlinda; Raya Sulistyowati (Jurnal Pendidikan Tata Niaga (JPTN), 2021)
The purpose of this research is to determine about the effect of the implementation of the cleanliness, health, safety, environment (CHSE) adaptation program on the satisfaction of visitors to tourist destinations in Kediri Regency in the new normal era which has an impact on the development of the tourism economy and creative industries. This type of research uses quantitative research with a descriptive approach. The data collection technique was carried out using an online questionnaire to respondents whose criteria had been determined by the researcher using a Likert scale of 1-5, which was distributed to 105 respondents. The data results were processed using IBM SPSS version 26.0 with data analysis techniques using path analysis. The results obtained that the variable implementation of the CHSE adaptation program (X) had a significant effect on visitor satisfaction (Z), visitor satisfaction (Z) had a significant effect on the economic development of tourism and the creative industry (Y), the implementation of the CHSE adaptation program (X) had a not significant effect on economic development. Tourism and creative industries (Y), and the implementation of the CHSE adaptation program (X) had a significant effect on economic development. Tourism and creative industries (Y) through visitor satisfaction (Z). Keywords: Adaptation program CHSE; tourist economy & creative industries; visitor satisfaction.